2020
DOI: 10.1002/ajh.26058
|View full text |Cite
|
Sign up to set email alerts
|

Loss of alpha‐globin genes in human subjects is associated with improved nitric oxide‐mediated vascular perfusion

Abstract: Alpha thalassemia is a hemoglobinopathy due to decreased production of the α‐globin protein from loss of up to four α‐globin genes, with one or two missing in the trait phenotype. Individuals with sickle cell disease who co‐inherit the loss of one or two α‐globin genes have been known to have reduced risk of morbid outcomes, but the underlying mechanism is unknown. While α‐globin gene deletions affect sickle red cell deformability, the α‐globin genes and protein are also present in the endothelial wall of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 34 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…For example, a recent study found that healthy individuals with alpha globin gene deletions have increased nitric oxide-mediated vascular perfusion. 48 We recently discovered alpha globin gene deletions to be associated with protection from chronic kidney disease and end-stage kidney disease. 49 These associations were independent of sickle cell trait and hemoglobin level, raising the possibility that protection is conferred via mechanisms involving the vascular functions of alpha globin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study found that healthy individuals with alpha globin gene deletions have increased nitric oxide-mediated vascular perfusion. 48 We recently discovered alpha globin gene deletions to be associated with protection from chronic kidney disease and end-stage kidney disease. 49 These associations were independent of sickle cell trait and hemoglobin level, raising the possibility that protection is conferred via mechanisms involving the vascular functions of alpha globin.…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulation of NO signaling by endothelial alpha globin is O 2 dependent, as both eNOS production of NO and deactivation of NO by alpha globin (producing nitrate, NO 3 − ) require O 2 . Recent work from human studies confirmed an role for endothelial alpha globin in NO catabolism, as alpha thalassemic individuals demonstrated increased flow-mediated dilation 14 .…”
Section: Introductionmentioning
confidence: 93%
“…Recently, motivated by in vitro data on α-globin in the myoendothelial junction, 5,6 Denton and colleagues showed in non-anemic, non-SCA subjects that flow-mediated vasodilation, a well-known measure of NO-mediated vascular function, was significantly better in α-trait subjects than in subjects without α-trait. 8 Thus, the mechanism proposed in vitro whereby α-globin expressed in the endothelial cells would bind, react with and oxidize NO to form nitrate, thus reducing NO levels and the resultant vasodilatory effects of NO, seems to be operative not only in non-SCA subjects but also in SCA patients. Our results suggest that the protective effect of α-trait from the development of several chronic complications in SCA could, in addition to its known effects on the RBC, be due to the effect of α-globin on the vascular system through its ability to regulate the NO diffusion from the endothelium to the smooth muscle cells of the vascular wall.…”
Section: Ibm Spss Statistics Chicago Il)mentioning
confidence: 99%